Serotype Specific Sequence for Multi Test Line Nucleic Acid Lateral Flow Development - Narendra Yoga Hendarta; Asmarani Kusumawati; Tri Wibawa; Abu Tholib Aman (Jurnal Sain Veteriner, 2021)
Dengue virus that causes dengue fever and dengue shock syndrome has 4 different serotypes. Serotyping is needed for diagnosing and surveillance activities of disease spreaders. Recently, the Nucleic Acid Lateral Flow (NALF) method has been developed to confirm the results of easy amplification without complicated equipment. The aim of this study was designing capture probe for serotyping dengue virus (DENV) using NALF method. We have conducted an analytical study to obtain four specific sequences of Dengue Virus serotypes to develop serotipe specific NALF. Several parameters were used to analyzed Dengue genome sequences i.e % GC content, target homology, length of 100% homology continue of non-specific bases, hybridization temperature, and secondary structure to estimate the probe's capture capability in the hybridization reaction. The capture probes were applied to NALF and assayed using single strand DNA sample to check its performance. The result of four specific sequence capture probes, DENV1, 2, 3, 4 were CACCAGGGGAAGCTGTACCCTGGTGGT, GTGAGATGAAGCTGTAGTCTCACTGG, GCACTGAGGGAAGCTGTACCTCCTTGCA, AGCCAGGAGGAAGCTGTACTTCTGGTGG. Application to fabricated NALF gave no cross hybridization with high stringency buffer assay.Keywords : capture probe; dengue virus;  hybridization; nucleic acid lateral flow; serotyping